2013
DOI: 10.1039/c3ja50077b
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-based chemical imaging reveals plumage patterns in a 150 million year old early bird

Abstract: Charles Darwin acknowledged the importance of colour in the natural selection of bird plumage. Colour can indicate age, sex, and diet, as well as play roles in camouflage, mating and establishing territories. Feather and integument colour depend on both chemical and structural characteristics and so melanosome structure and trace metal biomarkers can be used to infer colour and pigment patterns in a range of extant and fossil organisms. In this study, three key specimens of Archaeopteryx were subjected to non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 32 publications
6
71
1
1
Order By: Relevance
“…The keratin protein family incorporates high concentrations of amino acids rich in sulfur (31,32), whereas carbon and nitrogen are common to all amino acids and proteins. However, Recently, it has been demonstrated that certain trace elements, such as copper, sulfur, and calcium, are present in both fossil and modern melanosome-bearing tissues, and it has been suggested that these elements may be used as biomarkers for melanin-derived compounds in fossils (23)(24)(25). This is problematic, however, in that all Cu, S, and Ca are also derived from bacterially induced decay as well as many diagenetic processes (37,38).…”
Section: Discussionmentioning
confidence: 95%
“…The keratin protein family incorporates high concentrations of amino acids rich in sulfur (31,32), whereas carbon and nitrogen are common to all amino acids and proteins. However, Recently, it has been demonstrated that certain trace elements, such as copper, sulfur, and calcium, are present in both fossil and modern melanosome-bearing tissues, and it has been suggested that these elements may be used as biomarkers for melanin-derived compounds in fossils (23)(24)(25). This is problematic, however, in that all Cu, S, and Ca are also derived from bacterially induced decay as well as many diagenetic processes (37,38).…”
Section: Discussionmentioning
confidence: 95%
“…[6,50,51]), yet the search for ancient melanic pigments only began in earnest in the late 2000s following the proposal that feather traces might infer evidence of original hues and shades [7,52]. Since then, a number of investigations have used chemical markers and presumed fossil melanosomes to explore aspects of the biology and ecology of extinct animals, including colour [8,9,[53][54][55][56][57], behaviour [8,56] and physiology [10]. However, studies reporting remnant melanosomes have been met with controversy, and an alternative hypothesis has been put forth favouring a more conservative interpretation of the fossil microbodies as microbes colonizing the degrading tissues prior to burial [12,58].…”
Section: Melanin and Melanosomes In The Fossil Recordmentioning
confidence: 99%
“…[14,63]) or lacking in specificity and/or relevant comparative material to rule out alternative hypotheses (e.g. [55,64,65]). Most critically, many alleged melanosomes occur only as imprints ('mouldic melanosomes' [53]), a preservation mode that implies preferential degradation of the bodies relative to the surrounding substrate [12].…”
Section: Melanin and Melanosomes In The Fossil Recordmentioning
confidence: 99%
“…The composition and structure of beta-keratin suggest that it may persist in fossil material [25][26][27][28][29][30]. Furthermore, because this protein is not found in humans and is vertebrate specific; its identification eliminates the alternative hypotheses of human or microbial contamination, and when used with adequate controls is a good indicator of endogeneity.…”
Section: Introductionmentioning
confidence: 99%